Preparation of α-zein loaded with baicalincomposites: A study on their in vitro simulated digestive behavior and molecular dynamics simulation - RunCheng Zhou; QiLin Liang; Han Lei; Tianci Liang; Simin Chen; Xin Chen (Applied Biological Chemistry)
Abstract In order to improve the bioavailability of baicalin, this article prepared for α-zein loaded with baicalin composites (α-zein@BA) by pH driven method and they were characterized using scanning electron microscopy, infrared spectroscopy, and measurement of particle size distribution in water solution phase techniques. The digestive behavior and antioxidant activity of composites before and after simulating gastrointestinal fluid in vitro were studied as well. At the same time, molecular dynamics simulation techniques were used to reveal the molecular mechanism behind the formation of the composite between the two. The results indicated that the composites of α-zein@BA were observed to be approximately spherical under a scanning electron microscope, and their particle size was mainly distributed in the range of 94.55-145.10 μm in aqueous solution, whose encapsulation efficiency of baicalin was (86.61 ± 0.71) %. Infrared spectroscopy analysis indicated that α-zein and baicalin mainly formed complexes through hydrogen bonding, electrostatic and hydrophobic interactions. The measurement results of baicalin residue in simulated digestion of gastric and intestinal fluids in vitro are as follows: α-zein@BA > Baicalin, while both significantly increased in the gastric digestion stage (P < 0.05) and significantly decreased in the intestinal digestion stage (P < 0.05). Molecular dynamics simulation studies have shown that baicalin has a promoting effect on protein structural stability, and protein 158SER and GLN196 were mainly formed hydrogen bonds with it, while hydrophobic interactions were mainly manifested between non-polar amino acids such as PHE201 and PRO200. This study indicates that α-zein and baicalin can form stable composites, improving the bioavailability of baicalin.